GENDER ISSUES IN KHALED HOSSEINI’S NOVEL A THOUSAND SPLENDID SUNS - Harnum, Yuni Kartika; Burhamzah, Muftihaturrahmah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This article examined the gender issues in the novel ‘A Thousand Splendid Suns’ by Khaled Hosseini. The focus of this article is to analyze the forms of gender issues and how the characters Mariam and Laila deal with gender issues in the novel A Thousand Splendid Suns. The purpose of this research is to explore gender issues and how the characters Mariam and Laila deal with them. The method used in this research is descriptive-qualitative using a feminist literary criticism approach. The main data source in this study is the novel A Thousand Splendid Suns by Khaled Hosseini. After analyzing the novel, the researchers found that there were five gender issues experienced by Mariam and Laila, namely: (1) violence; (2) marginalization; (3) subordination; (4) stereotypes; and (5) double standards. Besides that, this research provides an overview of how the characters deal with gender issues by using education, awareness, and physical strength to fight their oppressors.